Răspuns :
x+3=3x-5
x-3x=-5-3
-2x=-8
x=4
2(x-2)=3 (2-x)
2x-4=6-3x
2x+3x=6+4
5x=10
x=2
x-3x=-5-3
-2x=-8
x=4
2(x-2)=3 (2-x)
2x-4=6-3x
2x+3x=6+4
5x=10
x=2
[tex]x + 3 = 3x - 5[/tex]
[tex]x - 3x = - 5 - 3[/tex]
[tex] - 2x = - 8 \: | \div ( - 2)[/tex]
[tex]x = 4[/tex]
[tex]2(x + 3) = 18[/tex]
[tex]2x + 6 = 18[/tex]
[tex]2x = 18 - 6[/tex]
[tex]2x = 12[/tex]
[tex]x = \frac{12}{2} [/tex]
[tex]x = 6[/tex]
[tex]2(x - 2) = 3(2 - x)[/tex]
[tex]2x - 4 = 6- 3x[/tex]
[tex]2x + 3x = 6 + 4[/tex]
[tex]5x = 10[/tex]
[tex]x = \frac{10}{5} [/tex]
[tex]x = 2[/tex]
[tex] {(x - 1)}^{2} = (x + 2)(x - 2)[/tex]
[tex] {x}^{2} - 2 \times x \times 1 + {1}^{2} = {x}^{2} - {2}^{2} [/tex]
[tex] {x}^{2} - 2x + 1 = {x}^{2} - 4[/tex]
[tex] {x}^{2} - 2x - {x}^{2} = - 4 - 1[/tex]
[tex] - 2x = - 5 \: | \times ( - 1)[/tex]
[tex]2x = 5[/tex]
[tex]x = \frac{5}{2} [/tex]
[tex]x = 2.5[/tex]
[tex]x - 3x = - 5 - 3[/tex]
[tex] - 2x = - 8 \: | \div ( - 2)[/tex]
[tex]x = 4[/tex]
[tex]2(x + 3) = 18[/tex]
[tex]2x + 6 = 18[/tex]
[tex]2x = 18 - 6[/tex]
[tex]2x = 12[/tex]
[tex]x = \frac{12}{2} [/tex]
[tex]x = 6[/tex]
[tex]2(x - 2) = 3(2 - x)[/tex]
[tex]2x - 4 = 6- 3x[/tex]
[tex]2x + 3x = 6 + 4[/tex]
[tex]5x = 10[/tex]
[tex]x = \frac{10}{5} [/tex]
[tex]x = 2[/tex]
[tex] {(x - 1)}^{2} = (x + 2)(x - 2)[/tex]
[tex] {x}^{2} - 2 \times x \times 1 + {1}^{2} = {x}^{2} - {2}^{2} [/tex]
[tex] {x}^{2} - 2x + 1 = {x}^{2} - 4[/tex]
[tex] {x}^{2} - 2x - {x}^{2} = - 4 - 1[/tex]
[tex] - 2x = - 5 \: | \times ( - 1)[/tex]
[tex]2x = 5[/tex]
[tex]x = \frac{5}{2} [/tex]
[tex]x = 2.5[/tex]